Vision-Related Quality of Life among Patients Attending the Diabetes and Eye Clinics in Kenyatta National Hospital, Kenya - Nerice Emade; Joseph Nyamori; Margaret Njuguna; Lucy Njambi; Stephen Gichuhi (Journal of Ophthalmology)
Importance. The increasing incidence of diabetes mellitus worldwide has resulted in an increase in microvascular complications such as diabetic retinopathy. Visual impairment, patients’ worries, and restrictions due to diabetes mellitus and diabetic retinopathy may affect patients’ quality of life. Objective. Our main objective was to determine the overall vision-related quality of life (VRQoL) among patients with diabetes mellitus attending the diabetes and eye clinics in Kenyatta National Hospital, Kenya. Design. Analytical cross-sectional study conducted in December 2020 setting: This study was performed at the Diabetes and Eye Clinics in Kenyatta National Hospital, the main national referral centre in Nairobi, Kenya. Participants. Using a purposive consecutive sampling method, we enrolled 100 participants, 50 with diabetic retinopathy and 50 without diabetic retinopathy. Main Outcomes and Measures. We compared the VRQoL of participants with diabetic retinopathy with those without diabetic retinopathy and assessed whether VRQoL worsened with increasing the severity of diabetic retinopathy. VRQoL was assessed using the World Health Organization/Prevention of Blindness and Deafness Vision Function-20 Questionnaire (VF-20). With this tool, the higher the mean score, the worse the quality of life. Diabetic retinopathy was graded using the Early Treatment of Diabetic Retinopathy Study. VRQoL trend with DR were analysed using the worse eye. Results. Participants with diabetic retinopathy had worse overall total VRQoL mean score (33.4, SD11.5) than those without (26.9, SD 4.7) in all domains; overall self-rating, 2.6 vs. 2.2, p<0.001; general functioning, 18.0 vs. 14.7, p=0.005; psychosocial, 6.7 vs. 5.3, p<0.001; and visual symptoms, 6.1 vs. 4.8, p<0.001. VRQoL was worse with increasing severity of diabetic retinopathy in all domains moving from mild NPDR to moderate NPDR, severe NPDR and PDR, overall self-rating (2.2, 2.5, 3.5, 3.3; p<0.001); visual symptoms (5.6, 5.6, 7.5, 7.4; p=0.002); psychosocial (5.7, 6.5, 6.0 8.8; p=0.004); and general functioning (15.7, 16.9, 17.5 23.6; p=0.014). Presence of DR, distance vision impairment, and diabetic macula oedema were associated with low overall self-rating. Conclusion and Relevance. Our findings underscore the need for interventions for early detection and management of diabetic retinopathy to prevent developing more advanced DR and its associated deterioration of VRQoL.